Amphidomataceae (Dinophyceae) in the western Greenland area, including description of Azadinium perforatum sp. nov. Issue 1 (2nd January 2020) - Tillmann, Urban; Wietkamp, Stephan; Krock, Bernd; Tillmann, Anette; Voss, Daniela; Gu, Haifeng
ABSTRACT: Azaspiracids (AZA) are lipophilic marine biotoxins associated with shellfish poisoning which are produced by some species of Amphidomataceae. Diversity and global biogeography of this family are still poorly known. In summer 2017 plankton samples were collected from the central Labrador Sea and western Greenland coast from 64° N (Gothaab Fjord) to 75° N for the presence of Amphidomataceae and AZA. In the central Labrador Sea, light microscopy revealed small Azadinium -like cells (9200 cells l −1 ). Clonal strains established from plankton samples and scanning electron microscopy of fixed plankton samples revealed at least eight species of Amphidomataceae: Azadinium obesum, Az. trinitatum, Az. dexteroporum, Az. spinosum, Az. polongum, Amphidoma languida, Azadinium spec., and a new species described here as Azadinium perforatum sp. nov . The new species differed from other Azadinium species by the presence of thecal pores on the pore plate. All samples, including cultured strains, filtered seawater samples, and solid phase adsorption toxin tracking (SPATT) samplers deployed during the expedition in a continuous water-sampling system (FerryBox), were negative for AZA. DNA samples and PCR assays were positive for Amphidomataceae from most stations, whereas species-specific assays for three toxigenic species were rarely positive (two stations for Az. poporum, one station for Am. languida ). The results highlight the presence of Amphidomataceae in the area but the lack of toxins and low abundance of toxigenic species currently indicate a low risk of toxic Amphidomataceae blooms in Arctic coastal waters.